The issue of providing children’s palliative care to forced migrants coming from conflict-affected areas: Review article (Paliativní medicína, 2023)
The article responds to the current migration wave regarding the war conflict in Ukraine and its impact on the provision of pediatric palliative care in the Czech Republic. It presents summary literature data on the situation of families receiving health care after migration, in the context of complex psychosocial impacts of resettlement and war conflict.Part of the text is a description of the barriers to the provision of health care to these families, which include the culturally conditioned needs of the family and patients, the language barrier and the specific challenges that the provision of care in this context poses to health professionals and hospital management.The text, based on available foreign literature, places the issue of war refugees with palliative needs in the context of our country, and in the end offers recommendations for the provision of pediatric palliative care in the Czech Republic.
Keywords: pediatric palliative care; cultural sensitivity; displaced families; war-forced migration; review article